The Surprising Sluggishness of French Exports: Reviewing Competitiveness and its Determinants - Charlotte Emlinger; Sébastien Jean; Vincent Vicard (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The large deterioration in France's current account balance during the euro's first decade was mainly due to its poor export performances. Although there have been no more market share losses since 2012, French export growth lags behind that of our European partners. Given that labor cost have grown more slowly in France than in Germany since 2011, the sluggishness of French export performance appears surprising. To date, however, the rebalancing of labor costs under way only represents between a quarter and a third of the divergence observed between 1999 and the crisis. Moreover, whether through social contribution exemptions in France or Germany's introduction of a minimum wage, the relative decrease has mainly concerned low wage brackets, which have little influence on exports. Such limited "catch-up" is symptomatic of the difficulty that the Eurozone has in implementing coordinated rebalancing policies across its Member States. The absence of any marked improvement in French export performances remains difficult to explain by traditional determinants. French specialisation has moved away from Germany's to become closer to Italy's, but this does not seem to have been particularly problematic. The hypothesis of a hysteresis effect, according to which the decline in French industrial production is at the origin of an inability to gain back export market shares, is not confirmed analysis. The unquestionable deterioration in non-price competitiveness remains a valuable explanation, but it is difficult to relate it to clearly identified causes, whether as regards quality or investment. Investment statistics suggest that France does not suffer from a lack of R&D expenditures in comparison with its principal neighbours; on the contrary, their level contrasts with the relative decline in manufacturing output. This finding raises the question of how far R&D activities have a ripple effect on French manufacturing. This aspect is even more important if one considers that France's economy is characterised by the major role played by its multinationals, whose activities abroad have grown more rapidly than those of other large Eurozone countries. The resulting foreign direct investment revenues do much to explain that France has a near equilibrium current account. In this respect, the French economy suffers more from a loss of industrial production sites than from any lack of competitiveness.
Keywords: 330